Plazemska krogla - Čekada, Miha (Vakuumist, 2001)
Plasma bass is an apparatus which maintains high-frequency discharges between the cetral electrode and the glass sphere. As a "fun physics" product it has no practical use, nevertheless it is appropriate for teaching the electricity conduction basics. The Tesla transformer which supplies high-frequency signal is also described.
Keywords: fizikalni poskusi; plazemska krogla; Teslov transformator